Some New First-Order All-Pass Realizations Using CCII. (2004) - Pal, Kirat; Rana, Seema
Abstract : Some new first-order all-pass filters using a second-generation current conveyor are reported. Two circuits have higher input impedance than reported very recently and use a grounded capacitor. Additionally two more circuits have been reported, one of which has minimum passive and active components and has the facility of single resistance tuning. The other circuit has high input impedance and uses two current conveyors but has one passive component less than the similar circuits reported earlier.